Delinquency, Self Esteem and Social Control: A Retroductive Analysis - Liu, William T. (The American catholic sociological review, 1963)
Data collected for two independent studies on delinquency suggested that, when class is under control, there exist significant differences between the two groups-delinquent and non-delinquent populations-with regard to self esteem, perceived opportunity, and reported problems with which subjects of the two groups are most concerned. The results of the two studies made it possible to re-conceptualize our research thinking on delinquency. During the process of retroductive thinking on our material, we suggest that (1) the Merton-Cloward model and the Short-Cohen model may be seen together as they both are dealing with delinquent attitudes with varied location of research foci; and (2) the attempt to use "delinquent status" as an independent variable rather than dependent variable with regard to other motivational correlates may be strategically important in delinquency research.